Design, Synthesis, and Biological Evaluation of Novel Pyrrolo [2, 3-b] Pyridine Derivatives for Nonalcoholic Fatty Liver Disease. (6th June 2022) - Ma, Jialin; Li, Jing; Yao, Dongping; Wang, Qi; Chen, Xinzhou; Tao, Feiyan; Chen, Bin; Xie, Yongmei; Bai, Lang; Zhang, Yiwen
Abstract : Nonalcoholic fatty liver disease (NAFLD) is featured with liver fat infiltration and accumulation with no connection with overdrinking. With the rising trends and no FDA-approved drugs, NAFLD attracts global attention. In this study, we successfully synthesized 18 novel SIS3 derivatives and evaluated them for pharmacological activity. F-9 and F-15 had potent weight-losing effects. Importantly, intraperitoneal administration of F-9 at 10 mg·kg −1 ·day −1 for 5 weeks had the most excellent effects to reduce the weight of the body, liver, and fat, as well as adjusting serum levels of AST, ALT, TC, TG, HDL, and LDL. H&E staining showed that F-9 could suppress fat deposition and increase the adipocyte size in the liver.